2014
DOI: 10.1002/mnfr.201300726
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methionine‐deficient and methionine‐supplemented diets on the hepatic one‐carbon and lipid metabolism in mice

Abstract: Our findings indicate that both dietary methionine deficiency and methionine supplementation can induce molecular abnormalities in the liver associated with the development of NAFLD, including deregulation in lipid and one-carbon metabolic pathways, and induction of oxidative and ER stress. These pathophysiological events may ultimately lead to lipid accumulation in the livers, triggering the development of NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 53 publications
7
29
0
Order By: Relevance
“…In a subsequent study, using a panel of 7 genetically diverse inbred mouse strains (14), we demonstrated that the development of a strain-dependent NASH-like liver injury induced by a 12-wk dietary choline-and folate deficiency is paralleled by a prominent dysregulation in lipid and 1-carbon metabolism. Similar findings were reported in the livers of mice fed a methionine-deficient diet for 10 wk (15).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…In a subsequent study, using a panel of 7 genetically diverse inbred mouse strains (14), we demonstrated that the development of a strain-dependent NASH-like liver injury induced by a 12-wk dietary choline-and folate deficiency is paralleled by a prominent dysregulation in lipid and 1-carbon metabolism. Similar findings were reported in the livers of mice fed a methionine-deficient diet for 10 wk (15).…”
supporting
confidence: 87%
“…The development of NASH and NASH-related liver carcinogenesis has been associated with genetic, genomic, and metabolic abnormalities, with alterations in hepatic lipid homeostasis being one of the most prominent (11). In our studies, using a mouse model of NAFLD induced by a choline-and folate-deficient (CFD) (12)(13)(14) or methioninedeficient (15) diet, we found that the development of NASH is characterized by a profound and interconnected dysregulation in hepatic folate-dependent 1-carbon and lipid metabolism. Specifically, feeding C57BL/6J and DBA/2J mice a CFD diet for 18 wk resulted in an extensive hepatic lipid accumulation, prominent alterations in methyl donor metabolism, and development of NASH (12).…”
mentioning
confidence: 96%
“…The data are consistent with Aissa et al. () and Tapiarojas et al. () who reported that excessive Met supplementation induced oxidative stress, possibly due to that dietary Met supplementation increased the levels of fatty acid synthesis and oxidation (Skiba‐Cassy, Geurden, Panserat, & Seiliez, ).…”
Section: Discussionsupporting
confidence: 91%
“…In mice, modulation of dietary methionine can alter Srebf expression by feedback induction (Aissa et al, 2014). Similarly, expression of methionine metabolism genes in C. elegans not only depends on SREBF1 (SBP-1), but also feeds back to control SREBF1 and affect lipid metabolism (Walker et al, 2011).…”
Section: Ec Signaling Regulates Methionine Metabolism Via Srebfsmentioning
confidence: 99%